Ce-Mo-based composite oxide ceramic, compact, sintered body, and article
By adding trace elements such as Al, Zr and Si to Ce-Mo composite oxide ceramics, the problem that their effects on antibacterial and antiviral properties have not been studied in the existing technology has been solved, and the antibacterial and antiviral properties of ceramics have been achieved. A huge increase in virality.
Patent Information
- Application Number
- CN202380014313.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-28
- Filing Date
- 2023-06-20
- Publication Date
- 2025-01-24
AI Technical Summary
In the prior art, composite oxide ceramics containing cerium and molybdenum have not been studied for the effects of antibacteriality and antivirality when mixed with other elements.
In the CE-MO series of composite oxide ceramics, the trace elements composed of free AL, ZR and SI are selected to ensure that its content reaches 270 ppm and exists in crystal phase to improve the dissolution of metal ions, thereby improving antibacteriality and antibacteriality and antibacteriality and antibacteriality and antibacteriality and antibacteriality and Anti -virus.
By adding trace elements, the antibacterial and antiviral properties of Ce-Mo composite oxide ceramics are significantly improved, and metal ions are more easily eluted, enhancing its bactericidal and virucidal effects.
Smart Images

Figure CN119365433A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to Ce-Mo composite oxide ceramics, powder compacts, sintered bodies and articles. Background Art
[0002] Inorganic antibacterial and antiviral agents have advantages such as a wide temperature range in which they can be used and difficulty in obtaining resistance to viruses, and have been actively studied in recent years. As such antibacterial and antiviral agents, metal systems such as Ag and Cu, photocatalyst systems such as TiO2, and metal oxide systems such as ZnO and CaO have been reported so far and have been actually used.
[0003] As shown in Patent Document 1, among inorganic antibacterial and antiviral agents, composite oxide ceramics containing cerium (Ce) and molybdenum (Mo) and having high antibacterial and antiviral activities have attracted particular attention.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: International Publication No. 2022 / 014631
[0007] (Problem to be solved by the invention)
[0008] Conventionally, when elements other than cerium, molybdenum and oxygen are mixed into composite oxide ceramics containing cerium and molybdenum, no research has been conducted on the effects of such elements on the antibacterial and antiviral properties of the composite oxide ceramics. Summary of the invention
[0009] An object of the present invention is to provide a Ce-Mo-based composite oxide ceramic or the like having excellent antibacterial and antiviral properties.
[0010] (Solutions used to solve problems)
[0011] The present inventors conducted in-depth research to achieve the aforementioned objectives and found that if a Ce-Mo composite oxide ceramic comprising a composite oxide of cerium (Ce) and molybdenum (Mo) contains at least one trace element selected from the group consisting of Al, Zr and Si, metal ions become easily eluted and excellent antibacterial and antiviral properties can be exerted, thereby completing the present invention.
[0012] The solution for solving the above-mentioned problems is as follows.
[0013] <1> A Ce—Mo-based composite oxide ceramic comprising cerium, molybdenum, and at least one trace element selected from the group consisting of Al, Zr, and Si.
[0014] <2> The Ce—Mo based composite oxide ceramic according to <1> above, wherein the content of the trace element is 270 ppm or more.
[0015] <3> The Ce—Mo based composite oxide ceramic according to <1> or <2>, wherein the trace element is present in a crystal phase.
[0016] <4> The Ce-Mo composite oxide ceramic according to <1> or <2>, comprising Ce2Mo3O 13 .
[0017] <5> A powder compact, wherein the Ce-Mo based composite oxide ceramic described in <1> or <2> is in powder form, and the powder compact is obtained by compression molding the powdered Ce-Mo based composite oxide ceramic.
[0018] <6> A sintered body obtained by sintering the Ce—Mo based composite oxide ceramics described in <1> or <2> above.
[0019] <7> An article having the Ce—Mo based composite oxide ceramic according to <1> or <2> above on at least a portion of its surface.
[0020] <8> An article comprising the Ce—Mo composite oxide ceramic according to <1> or <2> dispersed in a substrate.
[0021] Effects of the Invention
[0022] According to the present invention, it is possible to provide Ce-Mo based composite oxide ceramics and the like having excellent antibacterial and antiviral properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 A diagram showing a method (scheme) for producing Ce-Mo composite oxide ceramics according to Example 1 by a solid phase synthesis method
[0024] Figure 2 Graph showing the X-ray diffraction spectra of each pre-calcined powder of Example 1 and Comparative Example 1
[0025] Figure 3 Graph showing the pH behavior over time of pure water in which the pre-calcined powders of Example 1 and Comparative Example 1 were immersed DETAILED DESCRIPTION
[0026] The Ce—Mo-based composite oxide ceramics of the present embodiment contains cerium (Ce), molybdenum (Mo), and at least one trace element selected from the group consisting of Al, Zr, and Si.
[0027] Ce-Mo composite oxide ceramics are composite oxide ceramics containing cerium (Ce) and molybdenum (Mo), and contain the aforementioned trace elements as essential components. The composition ratio (molar ratio) of cerium (Ce) and molybdenum (Mo) contained in the Ce-Mo composite oxide ceramics is not particularly limited as long as it does not impair the purpose of the present invention, and for example, Ce:Mo=2:3 or Ce:Mo=1:2.
[0028] It should be noted that the amount of oxygen atoms (O) contained in the Ce-Mo based composite oxide ceramics may be a stoichiometric composition or may deviate from the stoichiometric composition. That is, the Ce-Mo based composite oxide ceramics may be an indefinite compound.
[0029] Examples of Ce-Mo composite oxide ceramics include Ce(MoO4)2, Ce2MoO6, Ce2(MoO4)3, Ce2Mo3O 13 、Ce2Mo4O 15 、Ce6(MoO4)8(Mo2O7)、Ce8Mo 12 O 49 These Ce-Mo composite oxide ceramics can be used alone or in combination of two or more. As Ce-Mo composite oxide ceramics, Ce2Mo3O 13 .
[0030] The aforementioned trace elements contained in the Ce-Mo based composite oxide ceramics may be present in any part of the Ce-Mo based composite oxide ceramics as long as they do not impair the purpose of the present invention, but are preferably present in the crystal phase of the Ce-Mo based composite oxide ceramics from the viewpoint of easily maintaining the Ce-Mo based composite oxide ceramics in a preferred crystal structure (e.g., a γ-type crystal structure).
[0031] As described above, the trace element is composed of at least one selected from the group consisting of Al, Zr and Si. As the trace element, aluminum is preferred, for example.
[0032] The content (content rate) of trace elements in Ce-Mo composite oxide ceramics is, for example, preferably 270 ppm or more, more preferably 500 ppm or more, and further preferably 700 ppm or more. It should be noted that the upper limit of the content (content rate) of trace elements in Ce-Mo composite oxide ceramics is not particularly limited as long as it does not impair the purpose of the present invention, and is, for example, preferably 100000 ppm or less, more preferably 75000 ppm or less, and further preferably 50000 ppm or less.
[0033] If the content (content ratio) of the aforementioned trace elements in the Ce-Mo composite oxide ceramics is within this range, the aforementioned trace elements penetrate into the crystal structure of the Ce-Mo composite oxides, change the crystal structure of the Ce-Mo composite oxides, and the metal ions constituting the crystal structure become easily eluted, and it is speculated that the pH decreases when the Ce-Mo composite oxide ceramics are added to water. As a result, it is speculated that the antibacterial and antiviral properties of the Ce-Mo composite oxide ceramics are higher than those of the Ce-Mo composite oxide ceramics that do not contain trace elements.
[0034] The detection of trace elements in the Ce-Mo based composite oxide ceramics is performed, for example, using an X-ray fluorescence spectrometer (XRF). Based on the detection results, the content (content ratio) of the trace elements in the Ce-Mo based composite oxide ceramics is determined.
[0035] Ce-Mo composite oxide ceramics may contain other elements (such as H, F, Ba, Zn, Mg, Fe, Y, etc.) other than the aforementioned trace elements as long as they do not impair the purpose of the present invention. For example, other elements may be contained in Ce-Mo composite oxide ceramics at 0.01 mass % or less (100 ppm or less), or 0.008 mass % or less (80 ppm or less). The aforementioned other elements in Ce-Mo composite oxide ceramics can be detected using a fluorescent X-ray spectrometer (XRF) or an ICP emission spectrophotometer (ICP).
[0036] Ce-Mo composite oxide ceramics can be crystalline in the form of single crystal or polycrystalline, or amorphous (amorphous) such as glass, or a combination of a crystalline part and an amorphous part. In addition, the crystal phase can be a single phase or a combination of two or more different phases.
[0037] The method for producing Ce-Mo composite oxide ceramics is not particularly limited as long as it does not impair the purpose of the present invention, and an example thereof may be a solid phase reaction method. As a method for producing Ce-Mo composite oxide ceramics, a solid phase reaction method is preferred from the viewpoint of easily adjusting the trace elements contained to a predetermined amount.
[0038] Here, a method for producing Ce-Mo based composite oxide ceramics by solid phase reaction method is exemplified. The method for producing Ce-Mo based composite oxide ceramics by solid phase reaction method includes, for example, a mixing step, a drying step, and a pre-calcining step.
[0039] The mixing step is a step of mixing a predetermined amount of a cerium compound, a predetermined amount of a molybdenum compound, and a predetermined amount of a trace element or a trace element compound to obtain a mixture thereof.
[0040] The cerium compound is a compound containing cerium (Ce) required for the manufacture of Ce-Mo composite oxide ceramics, and examples thereof include CeO2, cerium nitrate, cerium chloride, cerium sulfate, cerium hydroxide, cerium carbonate, cerium acetate, etc. As the cerium compound, at least one selected from the group consisting of CeO2, cerium nitrate, cerium chloride, cerium sulfate, cerium hydroxide, cerium carbonate, and cerium acetate is used. It should be noted that, as the cerium compound, CeO2 is preferred.
[0041] The molybdenum compound is a compound containing molybdenum (Mo) required for producing Ce-Mo composite oxide ceramics, and examples thereof include MoO3, MoO2, MoO, Mo(OH)3, Mo(OH)5, etc. As the molybdenum compound, at least one selected from the group consisting of MoO3, MoO2, MoO, Mo(OH)3, and Mo(OH)5 can be used. It should be noted that as the molybdenum compound, MoO3 is preferred.
[0042] The mixing ratio of the cerium compound and the molybdenum compound can be adjusted to Ce:Mo=2:3 in molar ratio, Ce:Mo=1:2 in molar ratio, Ce:Mo=1:1 in molar ratio, Ce:Mo=2:1 in molar ratio, Ce:Mo=3:4 in molar ratio, or Ce:Mo=3:5 in molar ratio. It should be noted that the mixing ratio of the cerium compound and the molybdenum compound is preferably Ce:Mo=2:3 in molar ratio.
[0043] In the preparation step, the trace element may be used alone, or a trace element compound containing the trace element may be used.
[0044] When the trace element is aluminum (Al), examples of the trace element compound (aluminum compound) include Al(NO3)3, Al2O3, aluminum sulfate, aluminum chloride, etc. As the aluminum compound, Al(NO3)3 is preferred.
[0045] When the trace element is zirconium (Zr), examples of the trace element compound (zirconium compound) include zirconium chloride, zirconium hydroxide, zirconium carbonate, zirconium sulfate, zirconium acetate, etc. As the zirconium compound, zirconium chloride is preferred.
[0046] When the trace element is silicon (Si), examples of the trace element compound (silicon compound) include silicon dioxide, silicon monoxide, silicon carbide, silicon nitride, etc. As the silicon compound, silicon dioxide is preferred.
[0047] The mixing ratio of the trace element compound to the cerium compound and the molybdenum compound is appropriately set so that the content (content ratio) of the trace element in the Ce—Mo-based composite oxide ceramic falls within the above-mentioned numerical range.
[0048] The mixing step is performed, for example, as follows: a predetermined amount of a cerium compound and a predetermined amount of a molybdenum compound are placed in a resin container (resin tank), and then a predetermined amount of a solvent such as a lower alcohol (ethanol) and a predetermined amount of a trace element compound are further placed in the container, and these are mixed for a predetermined time (e.g., 5 to 30 hours) using pebbles (zirconia pebbles, alumina pebbles, etc.). Through this mixing step, a slurry-like wet mixture is obtained.
[0049] The drying step is a step of drying the slurry-like wet mixture obtained after the mixing step. There is no particular limitation on the method for drying the wet mixture as long as it does not impair the purpose of the present invention, and examples thereof include drying by scalding with boiling water, drying by using a vibration dryer, and drying by using a spray dryer.
[0050] After the drying step, the wet mixture is dried into a powdery state. The obtained powdery mixture (mixed powder) is in a state where the cerium compound in a solid phase, the molybdenum compound in a solid phase, and the trace element compound (or trace element) are mixed with each other.
[0051] The pre-baking process is a process of calcining the mixed powder obtained after the drying process in a solid phase state. For example, the pre-baking process is as follows: the mixed powder is calcined at a temperature of 400°C to 650°C for 1 to 24 hours. The pre-baking process is carried out in a normal air atmosphere and does not need to be carried out in a special synthetic air atmosphere. It should be noted that the purpose of the pre-baking process is not to sinter the cerium compound, molybdenum compound, etc. in the mixed powder.
[0052] The pre-baked powder (an example of Ce-Mo based composite oxide ceramics) formed of a reaction product of the cerium compound, the molybdenum compound, and the trace element compound (or the trace element) is obtained through the pre-baked step.
[0053] The pre-baked powder can be granulated into a granular form by spray drying or the like as needed. Such granular form can be used as Ce-Mo based composite oxide ceramics.
[0054] In addition, the pre-baked powder can be formally calcined, and the sintered body can be used as a Ce-Mo composite oxide ceramic. For example, the pre-baked powder is compressed into a predetermined shape (e.g., a cylindrical shape, a disc shape, etc.) using a predetermined pressing machine, and the obtained molded body (compressed powder body) is calcined for 1 hour to 24 hours under predetermined temperature conditions (e.g., above 100°C and below 650°C) to obtain a sintered body that can be used as a Ce-Mo composite oxide ceramic.
[0055] The main calcination step is a calcination step for sintering the Ce-Mo based composite oxide ceramic in the pre-calcined powder, and can be performed in an air atmosphere.
[0056] In addition, the Ce—Mo-based composite oxide ceramics of the present embodiment can also be suitably produced by applying, for example, the citric acid polymerization method or the hydrothermal synthesis method described in International Publication No. 2022 / 014631.
[0057] The Ce-Mo composite oxide ceramic of the present embodiment shows antibacterial properties (antibacterial activity) and antiviral properties (antiviral activity) in the state before sintering. In addition, the Ce-Mo composite oxide ceramic of the present embodiment also shows antibacterial and antiviral properties after sintering as before sintering. Such Ce-Mo composite oxide ceramics can be used as an antibacterial agent with antibacterial properties, an antiviral agent with antiviral properties, and an antibacterial and antiviral agent having both antibacterial and antiviral properties.
[0058] The antibacterial and antiviral properties of Ce-Mo composite oxide ceramics can be evaluated, for example, by a thin film sealing method in accordance with JIS R 1756. For example, for Ce-Mo composite oxide ceramics, the virus reduction rate after 24 hours by the thin film sealing method is 99% or more.
[0059] The shape of the Ce-Mo composite oxide ceramic of the present embodiment is not particularly limited as long as it does not impair the purpose of the present invention, and can be formed into a desired shape according to the application. For example, the Ce-Mo composite oxide ceramic can be in the form of a powder, or it can be a granular form obtained by granulating the aforementioned powder by a spray drying method or the like. In addition, the Ce-Mo composite oxide ceramic can also be used in the form of a pressed powder body formed by compression molding a powdered ceramic material. In addition, the Ce-Mo composite oxide ceramic can also be used in the form of a sintered body.
[0060] In addition, Ce-Mo composite oxide ceramics can be used in the form of being applied to at least a portion of the surface of an article. The raw materials constituting the article to which Ce-Mo composite oxide ceramics are applied are not particularly limited as long as they do not impair the purpose of the present invention, and examples thereof include glass, ceramics, synthetic resins such as thermoplastic resins and thermosetting resins, rubber (natural rubber, synthetic rubber), genuine leather (natural leather), synthetic leather, metal materials formed of metals or alloys, wood, paper, fiber, nonwoven fabric, silicon (silicon wafers, etc.), carbon raw materials, minerals, gypsum, and the like.
[0061] In addition, the Ce-Mo composite oxide ceramics can also be used in the form of being dispersed in a predetermined substrate. As the substrate in which the Ce-Mo composite oxide ceramics are dispersed, there is no particular limitation as long as it does not impair the purpose of the present invention, and examples thereof include glass, ceramics, synthetic resins such as thermoplastic resins and thermosetting resins, rubber (natural rubber, synthetic rubber), synthetic leather, metal materials formed of metals or alloys, paper, fibers, nonwoven fabrics, carbon raw materials, minerals, gypsum, and the like.
[0062] Hereinafter, the present invention will be further described based on examples. It should be noted that the present invention is not limited to these examples.
[0063] [Example 1]
[0064] Prepare CeO2 as a cerium compound, prepare MoO3 as a molybdenum compound, and prepare Al(NO3)3 as a trace element compound (aluminum compound). Then, weigh the raw material powder of the cerium compound and the raw material powder of the molybdenum compound in a molar ratio of 2:3 (Ce:Mo=2:3). Put the weighed raw material powders into a resin container (resin can), and then further put a specified amount of ethanol and a specified amount of trace element compound (Al(NO3)3) into the container, and mix them for 24 hours using zirconium oxide cobblestone (blending process). The obtained slurry-like wet mixture is dried by boiling water to obtain a mixed powder (drying process). It should be noted that in the mixed powder, the cerium compound in a solid phase, the molybdenum compound in a solid phase, and the trace element compound are mixed with each other.
[0065] Next, the mixed powder is pre-baked for 1 hour at 475° C. in an air atmosphere to obtain a pre-baked powder (Ce-Mo composite oxide ceramic) formed by the reaction product of the cerium compound, the molybdenum compound and the trace element compound. Figure 1 Detailed Description of the Invention A method (scheme) for producing Ce-Mo based composite oxide ceramics according to Example 1 by a solid phase synthesis method is shown in FIG.
[0066] [Comparative Example 1]
[0067] A pre-calcined powder consisting of a reaction product of a cerium compound and a molybdenum compound was obtained in the same manner as in Example 1 except that the trace element compound (aluminum compound) was not mixed with the raw material powder of the cerium compound and the raw material powder of the molybdenum compound.
[0068] [Specification of crystal phase using XRD]
[0069] The crystal phase of each pre-calcined powder of Example 1 and Comparative Example 1 was identified by powder X-ray diffraction (XRD). The measurement conditions are as follows.
[0070] <Measurement conditions>
[0071] Measurement device: Powder X-ray diffraction device (device name: "Smart lab", manufactured by Rigaku Corporation)
[0072] Detector: D / teX Ultra250.
[0073] Optics: Focusing optics Bragg-Brentano type
[0074] X-ray power: 40kV-30mA
[0075] Step width: 0.0100°
[0076] Scan axis: 2θ / θ
[0077] Scanning range: 10.00°~80.00°
[0078] <Measurement Results>
[0079] The XRD measurement results (X-ray diffraction spectrum) are shown in Figure 2 . Figure 2 Graph showing the X-ray diffraction spectra of each pre-calcined powder of Example 1 and Comparative Example 1. Figure 2 The upper side shows the measurement results of Example 1. Figure 2 The lower side shows the measurement results of Comparative Example 1. Figure 2 The X-ray diffraction peaks of the measurement results shown below confirm that the pre-calcined powder of Comparative Example 1 has Ce2Mo3O 13 of the crystal structure.
[0080] In addition, for the pre-calcined powder of Example 1, according to Figure 2 The X-ray diffraction peaks of the measurement results shown on the upper side of the , confirm that, similarly to Comparative Example 1, Ce2Mo3O 13It should be noted that the crystal phase of the pre-calcined powder of Example 1 is inferred to contain not only Ce2Mo3O 13 , and also contains aluminum (Al) as a trace element. That is, it is speculated that the Ce2Mo3O 13 (Ce-Mo based composite oxide ceramics) A part of its elements is replaced by aluminum (trace element).
[0081] 〔pH behavior when immersed in pure water〕
[0082] The pre-baked powder (100 mg) of Example 1 was immersed in pure water (100 ml) in a glass container, and the pure water containing the pre-baked powder was stirred and mixed. Then, the time when the pre-baked powder was immersed was set to 0 hours, and the pH behavior of the pure water containing the pre-baked powder was measured over time using a pH meter. In addition, for the pre-baked powder of Comparative Example 1, the pH behavior of the pure water containing the pre-baked powder was also measured over time. The results are shown in Figure 3 .
[0083] Figure 3 It is a figure (graph) which shows the pH behavior over time of the pure water in which each pre-calcined powder of Example 1 and Comparative Example 1 was immersed. Figure 3 In the figure, the solid line corresponds to Example 1, and the dotted line corresponds to Comparative Example 1. Figure 3 As shown in the figure, it was confirmed that, at any time, the pH value of Example 1 was smaller than that of Comparative Example 1, and the acidity was higher. It is speculated that the influence of aluminum (trace element) contained in the pre-calcined powder of Example 1 on the Ce-Mo composite oxide ceramic (Ce2Mo3O 13 ) changes in the crystal structure, thereby making it easier for metal ions to elute from the pre-calcined powder, and thus the pH of the pure water in which the pre-calcined powder is immersed is lowered.
Claims
1. A Ce-Mo based composite oxide ceramic comprising: cerium, molybdenum, and at least one trace element selected from the group consisting of Al, Zr, and Si.
2. The Ce-Mo composite oxide ceramic according to claim 1, wherein: The content of the trace elements is above 270 ppm.
3. The Ce-Mo composite oxide ceramic according to claim 1 or claim 2, wherein: The trace elements are present in the crystalline phase.
4. The Ce-Mo composite oxide ceramic according to claim 1 or claim 2, comprising Ce2Mo3O 13 .
5. A powder compact, wherein: The Ce-Mo based composite oxide ceramics according to claim 1 or claim 2 is in powder form, and the powder compact is obtained by compression molding the powdered Ce-Mo based composite oxide ceramics. 6 . A sintered body obtained by sintering the Ce—Mo based composite oxide ceramic according to claim 1 or claim 2. 7 . An article having the Ce—Mo based composite oxide ceramic according to claim 1 or 2 on at least a part of its surface.
8. An article, wherein the Ce-Mo based composite oxide ceramic according to claim 1 or claim 2 is dispersed in a substrate.
Citation Information
Patent Citations
Complex oxide ceramic, functional material, and article
WO2022014631A1
Molybdenum-based temperature-stable microwave medium ceramic and preparation method thereof
CN104177085A
Molybdenum rare earth metal oxide catalyst as well as preparation method and application thereof
CN109718759A